Подолання логістичного пробілу: Smart-Synergy та штучний інтелект у побудові стійких мереж постачання - Севастьянов, Р.В. (Управління економікою: теорія та практика, 2025)
У статті розглянуто феномен «логістичного пробілу» в українській економіці як систематичну невідповідність між потребами ринку та фактичними можливостями існуючих ланцюгів постачань в умовах тривалих шоків, воєнних ризиків та регуляторного тиску (ESG, «зелений курс»). Запропоновано концепцію переходу від вразливих лінійних ланцюгів постачань до стійких багаторівневих логістичних мереж на основі моделі Smart-Synergy. Особливу увагу приділено ролі штучного інтелекту в трансформації ланцюгів постачань: від прогнозування попиту та виявлення вузьких місць до сценарного моделювання, оптимізації маршрутів, управління ризиками та підтримки прийняття рішень у реальному часі. The article examines the phenomenon of the “logistics gap” in the Ukrainian economy as a systematic mismatch between market needs and the actual capabilities of existing supply chains under conditions of prolonged shocks, war-related risks, and regulatory pressure (ESG, the “Green Deal”). The author proposes a concept for transitioning from vulnerable linear supply chains to sustainable multi-level logistics networks based on the Smart-Synergy model, which combines resilient logistics (ResiLog), flexible infrastructure solutions under the “logistics as a service” model (FlexHub), environmentally oriented innovations (GreenChain, ReLoop Logistics), as well as the intelligent components SmartFlow, DataChain, and CrowdRoute. Special attention is paid to the role of artificial intelligence in transforming supply chains: from demand forecasting and bottleneck detection to scenario modelling, route optimization, risk management, and real-time decision support. Based on a systematization of approaches to building adaptive logistics ecosystems, the article demonstrates how the integration of Smart-Synergy and AI solutions can help narrow the logistics gap, reduce CAPEX and OPEX, decrease disruption-related losses and the carbon footprint, and enhance the investment attractiveness of Ukrainian enterprises by ensuring compliance with contemporary requirements of international markets and post-war reconstruction programmes. The article formulates practical guidelines for business and public policy on a phased transition to sustainable logistics networks capable of supporting economic growth and recovery under conditions of high uncertainty.